Understanding Attitude to Public Transport and Private Vehicle - Syafieq Fahlevi Almassawa; Rissa Hanny (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
This study presents the results of qualitative research on the use of public transportation with private cars to understand attitudes. Some of the problems identified include: (1) an increase in the number of private vehicles in 2012-2015 by an average of 20 percent when compared to the number of existing roads and causing social problems so that it is necessary to reduce the use of private cars and increase the use of public transportation as a solution; (2) improve public transportation services following the expectations of users of transportation services; and (3) travel demand management is developed that public transport facilities are in line with demand. This study uses a qualitative approach with descriptive analysis with data collection methods using in-depth interviews and focuses on group discussions with parties related to this research. The study's conclusion shows that people want convenience in using public transportation, namely comfort, security, low cost, and integration.